2013
DOI: 10.7903/cmr.11370
|View full text |Cite
|
Sign up to set email alerts
|

Service Recovery in The Australian Banking Industry

Abstract: Considering the importance of service recovery as a corrective measure for service failures, this paper explores: (a) when Australian customers complain (b) the process they follow to look for solutions to their complaints and (c) how they evaluate banks' service recovery efforts. To address these objectives, 25 in-depth interviews were conducted with Australian retail banking customers. Results show that the main reasons for complaints were incorrect transactions, performance not meeting expectations, and unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Casado et al (2011) also revealed that lower levels of explanations and distributive justice and higher levels of dissatisfaction with service recovery increase the probability of complaint and exit of banking customers in Spain. In a study to examine service recovery of Australian banks, Valenzuela et al (2013) found that the concepts pertaining to fairness (procedural, interactive, and distributive) were found to be highly relevant in consumers' evaluations of service recovery efforts of Australian banks.…”
Section: Service Recoverymentioning
confidence: 99%
“…Casado et al (2011) also revealed that lower levels of explanations and distributive justice and higher levels of dissatisfaction with service recovery increase the probability of complaint and exit of banking customers in Spain. In a study to examine service recovery of Australian banks, Valenzuela et al (2013) found that the concepts pertaining to fairness (procedural, interactive, and distributive) were found to be highly relevant in consumers' evaluations of service recovery efforts of Australian banks.…”
Section: Service Recoverymentioning
confidence: 99%
“…This is necessitated to prevent the loss of a valued customer, which is especially penalizing for the banking industry as their success depends on the ability to tackle service failures and preserve long-term customer relationships (Laczniak et al, 2008). Valenzuela et al (2013) argue that banks need to make extra efforts to provide reliable service delivery every time and prevent dissatisfactory service experiences for consumers.…”
Section: Introductionmentioning
confidence: 99%
“…, 2008). Valenzuela et al. (2013) argue that banks need to make extra efforts to provide reliable service delivery every time and prevent dissatisfactory service experiences for consumers.…”
Section: Introductionmentioning
confidence: 99%